Analysis Validation of Interactive Flipbook-Based Teaching Materials To Increase Interest in Learning and The Character of “Gotong Royong” In Primary School Students - ., Nafiah; Ghufron, Syamsul; Hartatik, Sri; Mariati, Pance (Journal of Posthumanism, 2025)
This research focuses on developing flipbook-based interactive teaching materials to increase elementary school students’ interest in learning and the cooperative character of elementary school students. The background of this research is based on the importance of interactive learning media in improving the quality of education in the digital era, especially in instilling character values ​​such as mutual cooperation. This research aims to test the feasibility and practicality of flipbook-based teaching materials in increasing elementary school students’ interest in learning and the cooperative character of elementary school students. This research method uses a quantitative research approach, a type of experimental research. This research is a continuation of last year’s research which carried out a needs analysis and created a product draft, at this stage development and dissemination were carried out. The test subjects in this research were teachers and students SDN Magerejo 1, SDN Magerejo VI, SD Kyai Ibrahim, SDN Sidosermo 1, SD Taquma Surabaya. The data collection technique used was a questionnaire. The research instrument used in this research uses a questionnaire that has been validated by experts and all instruments created have been declared suitable for use by instrument experts. The data analysis technique used uses descriptive statistics. The results show that this flipbook-based teaching material is very feasible and practical, and is able to increase students’ interest in learning and the cooperative character of students. It is hoped that this research can become a model for the development of other technology-based teaching materials and contribute to improving the quality of education in Indonesia. The research output in the form of the resulting article will be submitted to an international journal indexed by Scopus as the final output of this research.